Nutritional Status of Children with Newly Diagnosed Food Allergies - Martyna Jasielska; Anna Buczyńska; Piotr Adamczyk; Urszula Grzybowska-Chlebowczyk (MDPI AG, 2023)
Background: Most published pediatric guidelines on food allergy highlight the importance of nutritional counseling and dietary adequacy to avoid either growth retardation or nutritional deficiencies. The aim of the study was an assessment of the nutritional status of children with IgE-mediated food allergies. Material and method: 45 patients with newly diagnosed food allergy (FA) and 33 healthy controls were analyzed (aged 6 to 72 months, 60.2% boys). The nutritional status was assessed using anthropometric measurements (body weight and length) and serum laboratory tests. The results were analyzed with the Statistica 12 software (Tulsa, OK, USA). Results: 82%, 40%, 8.8%, and 6.6% of the studied children demonstrated allergy to hen's egg, cow's milk, pork meat, and wheat/rye, respectively. Z-score BMI < −2SD was more often found in the FA subjects under 30 months of age than in the controls (p = 0.04). As many as 77.8% of the FA subjects and 78.8% of the controls were of normal height (hSDS: −0.23 ± 1.74 and −0.31 ± 1.49, respectively, p = 0.8). Retinol binding protein four serum concentration was significantly lower in the FA group (17.01 ± 3.84 mg/L) than in the controls (20.47 ± 4.87 mg/L, p < 0.001). No statistically significant differences were observed between the FA group and the controls (either in the younger or the older age group) (p > 0.05) for the serum concentrations of total protein, total cholesterol, thyroxin-binding prealbumin (TBPA), 25(OH)D, hemoglobin level or white blood cells. Conclusions: In patients under 30 months of age, one of the symptoms of food allergy may be body weight deficiency, while short stature is less common at the time of diagnosis.